DOI: 10.14264/uql.2015.464
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the role of the ErbB4 receptor in cardiomyocyte hypertrophy and adult cardiac function

Abstract: ErbB receptors (ErbB1 -ErbB4) are a subfamily of tyrosine kinase receptors that regulate cell proliferation and differentiation. It has been proposed that the ErbB1 subtype is transactivated by Ang II to mediate cardiac hypertrophy. However, whether other ErbB receptors, in particular the abundant subtype ErbB4, are involved in this process is not known. ErbB4 has four isoforms due to alternative splicing, each of which might play a distinct role in regulating cell activity. However, the role of individual Erb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 286 publications
(477 reference statements)
0
1
0
Order By: Relevance
“…The protein functions in the maintenance of the heart, central nervous system, intestinal tract, stomach, and mammary tissue. Wang (2015) found that activated ErbB4 was necessary for heart development and cardiac muscle cells; Almohazey and Frey (2015) and Takahashi et al (2015) showed that ErbB4 gene mutations were closely linked with mental illness such as schizophrenia, bipolar disorder, and amyotrophic lateral sclerosis. Schumacher et al (2015) suggested that ErbB4 receptor tyrosine kinase could cause lesions in the colon epithelium in inflammatory bowels.…”
Section: Introductionmentioning
confidence: 99%
“…The protein functions in the maintenance of the heart, central nervous system, intestinal tract, stomach, and mammary tissue. Wang (2015) found that activated ErbB4 was necessary for heart development and cardiac muscle cells; Almohazey and Frey (2015) and Takahashi et al (2015) showed that ErbB4 gene mutations were closely linked with mental illness such as schizophrenia, bipolar disorder, and amyotrophic lateral sclerosis. Schumacher et al (2015) suggested that ErbB4 receptor tyrosine kinase could cause lesions in the colon epithelium in inflammatory bowels.…”
Section: Introductionmentioning
confidence: 99%